Attachment styles, grief responses, and the moderating role of coping strategies in parents bereaved by the Sewol ferry accident. (30th November 2017) - Huh, Hyu Jung; Kim, Kyung Hee; Lee, Hee-Kyung; Chae, Jeong-Ho
ABSTRACT: Background : Previous studies on the influence of different types of attachment on grief responses have yielded contradictory outcomes. Little research has been conducted to identify the psychological processes that moderate the relationship between attachment representations and patterns of grief in disaster-related grief. Objective : The present study examines the effects of different attachment types on the grief responses of parents bereaved by loss of a child in a ferry accident, along with the moderating role of coping strategies. Methods : Bereaved parents ( n = 81) completed self-report questionnaires evaluating attachment, coping strategies, complicated grief, and shame/guilt. We performed correlational analyses to examine the associations among variables. We also conducted hierarchical regression analyses and simple slope analyses to examine the moderation effects of coping strategies. Results : Anxious attachment was associated with severe shame/guilt, and avoidant attachment correlated with complicated grief. Anxious attachment was positively associated with all types of coping strategies, and avoidant attachment was negatively related to problem- and emotion-focused coping. The use of problem-focused coping strategies was a significant moderator of the relationship between the avoidant attachment dimension and shame/guilt. Avoidant attachment had a significant effect on shame/guilt in groups with a high level of problem-focused coping. In contrast, none of the coping strategies significantly moderated the relationship between anxious attachment and grief response. Conclusions : The results suggest that people with highly avoidant attachment might be overwhelmed by shame and guilt when they try to use problem-focused coping strategies. This finding suggests that grief interventions should be organized with consideration of individual differences in attachment representations.